Analysis Translation Techniques of English-Indonesian on Student's Perception - Aulia Yunus; Ayumi Seftina; Farida Repelita Waty Kembaren; Namira Syaharani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this research is to explore how students employ different translation techniques, finding out how students use translation techniques, to compare our research with previous research. Then, to broaden the author's insight, and make it easier for readers to understand how important it is for students to use translation.Â This study employs a descriptive qualitative research design.There were 20 participants Through the analysis of questionnaire responses, internal and environmental factors that contribute to the challenges faced by English students in writing and finishing their research papers have been identified. In this findings and discussion The researcher wants to determine how many of them understand the use of translation techniques in English to Indonesian in carrying out their assignments. And we found around 50 percent of students understand the use of translation techniques. Translation techniques are the tools and strategies used by translators to convey the meaning of a text from the source language to the target language while preserving its essence and context. Understanding how students at this stage of their education employ these techniques can provide insights into their language proficiency and translation competence.